Evaluasi Penerapan Total Quality Management pada Bank BSI KCP Sengkang dalam Menghadapi Persaingan Perbankan Digital - Andi Yuniarti; Asriani; Nurwindah; Andi Nur Azisah (Precise Journal of Economic, 2025)
The rapid development of digital banking has intensified competition in the financial services industry, including Islamic banking. Bank Syariah Indonesia (BSI) Sengkang Branch Office is required to continuously improve service quality and operational performance to compete in the digital era. One management approach that can be applied to improve organizational performance is Total Quality Management (TQM). This study aims to evaluate the implementation of TQM at Bank Syariah Indonesia Sengkang Branch Office, Sudirman, in facing digital banking competition. This research used a qualitative descriptive approach using literature review and field observation methods. The results indicate that the application of TQM principles, such as customer focus, continuous improvement, employee engagement, and leadership commitment, plays a significant role in improving service quality and customer satisfaction. However, challenges remain in terms of adapting human resources and optimizing digital services. Therefore, consistent implementation of TQM is necessary to strengthen the competitiveness and excellence of Islamic banking services in the digital era